Prevalence and Correlates of Cardiovascular Calcification and Its Prognostic Effects Among Patients With Chronic Kidney Disease: Results From the C-STRIDE Study - Wang, Lan; Cheng, Hong; Zou, Xinrong; Yuan, Jun; Wu, Wenjing; Han, Siping; Wang, Jinwei; Zhang, Luxia; He, Kevin; Zhao, Ming-Hui; Wang, Xiaoqin (Frontiers in Public Health, 2022)
Background and Aims: The purpose of this study was to identify the characteristics and risk factors for cardiovascular calcification, and its relationship to prognosis, in patients with chronic kidney disease (CKD) stages 1–4. Methods: Cardiovascular calcification was evaluated at baseline by lateral abdominal radiography to detect abdominal aortic calcifications (AAC), and by echocardiogram to detect cardiac valvular calcifications (CVC), respectively. Demographic and laboratory data were collected and analyzed. Univariate and multivariable logistic regression model was used to explore the factors associated with the indicators of cardiovascular calcification, while Cox proportional hazards regression was used to examine the association between AAC/CVC and incidence of cardiovascular events and all-cause mortality. Results: A subgroup of 2,235 patients with measurement of AAC in the C-STRIDE study and a subgroup of 2,756 patients with CVC were included in the analysis. AAC was present in 206 patients (9.22%) and CVC was present in 163 patients (5.91%). Age, gender, history of cardiovascular diseases, smoking, hypertension, diabetes, levels of hemoglobin, low-density lipoprotein cholesterol, and uric acid were associated with prevalence of AAC, while only age, history of cardiovascular diseases, levels of serum albumin and low-density lipoprotein cholesterol were associated with prevalence of CVC (all p < 0.05).Survival analyses showed that cardiovascular events and all-cause mortality were significantly greater in patients with AACor with CVC (all p-values for log-rank tests <0.05). After adjustment for age, sex and estimated glomerular filtration rate (eGFR), AAC was associated with increased risk of all-cause mortality (hazard ratio = 1.67[95% confidence interval: 0.99, 2.79]), while CVC associated with that of cardiovascular events only among patients with comparatively normal eGFR (≥45 ml/min/1.73m2) (hazard ratio = 1.99 [0.98, 4.03]). Conclusion: Demographic and traditional cardiovascular risk factors were associated with cardiovascular calcification, especially AAC. AAC may be associated with risk of death for patients CKD of any severity, while CVC as a possible risk factor for cardiovascular disease only among those with mild to moderate CKD. Assessments of vascular calcification are need to be advanced to patients in the early and middle stages of chronic kidney disease and to initiate appropriate preventive measures earlier.